HUBUNGAN KOMUNIKASI INFORMAL DENGAN EFEKTIVITAS KERJA KARYAWAN PADA BAGIAN PENGEMBANGAN KARIR KARYAWAN BIRO KEPEGAWAIAN SEKRETARIAT DAERAH PROPINSI JAWA BARAT - Nur Azizah; Riffka Fauzany (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to determine whether there is a relationship between Informal Communication and Work Effectiveness of Employees in the Career Development Section of the Regional Secretariat of the Regional Secretariat of West Java Province. The problems studied in this study relate to the existence of low employee performance and effectiveness in the Career Development Section of the Regional Secretariat of the Regional Secretariat of West Java Province. The research method used is descriptive analytical method. The data analysis technique used is correlation test using Rank Spearman correlation and hypothesis testing using t-student test. The results of the study, the employee's perception of the Informal Communication Program is "medium". Meanwhile, for shows the employee's perception of the employee's work effectiveness is "high". Informal Communication with Employee Work Effectiveness in the Career Development Section of the Regional Secretariat of West Java Province, in general, is good. However, the organization must further enhance cooperation so that the working relationship can be established properlySo the hypothesis "There is a Positive Relationship between Informal Communication with Employee Work Effectiveness", can be accepted. Keywords : Informal Communication, Employee Work Effectiveness